Meta-analysis and brain imaging data support the involvement of VRK2 (rs2312147) in schizophrenia susceptibility - Li, Ming; Rietschel, Marcella (Schizophrenia research, 2012)
Recent genome-wide association studies have reported a set of schizophrenia susceptibility genes, but many of them await further replications in additional samples. Here we analyzed 5 genome-wide supported variants in a Han Chinese sample, and the variant rs2312147 at VRK2 showed significant association, which was confirmed in the meta-analysis combining multiple Asian and European samples (P = 3.17 × 10− 4, N = 7498). Rs2312147 is also associated with brain structure in healthy subjects, including the total brain volume and the white matter volume. Gene expression analyses indicated an up-regulation of VRK2 in schizophrenia patients. Our data provide further evidence for the contribution of VRK2 to schizophrenia.
Gesehen am 30.10.2018